THE ANALYSIS OF TEACHER-MADE TEST ITEMS IN MADRASAH IBTIDAIYAH EXAMINATIONS USING THE RASCH MODEL - Rahman, M. Saufi; Norhayati, Norhayati (Al-Mubtadi: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study aimed to analyze the quality of teacher-made tests in the Madrasah Examination for the Fikih of sixth-grade at Madrasah Ibtidaiyah Negeri 2 Hulu Sungai Tengah. The study employed quantitative evaluation method involving 125 students as research participants. The instrument analyzed consisted of 20 items. Data analysis was conducted using the Winsteps program to determine the fit of the test items to the Rasch model and to identify the characteristics of item difficulty levels. The results showed that all test items met the model fit criteria based on the MNSQ, ZSTD and Pt-Measure Corr values. These findings indicate that the instrument was able to measure students’ abilities appropriately. The item difficulty analysis revealed that 18 items were categorized as good difficulty levels because they measure values within the range of -2.0 to +2.0. The distribution of items was still dominated by easy and moderate questions, indicating that the measurement of students’ HOTs not been optimal. This study concludes that teacher-made tests still require improvement in terms of difficulty level distribution and the development of HOTs, to provide important implications for teachers to improving the quality of learning through the development of instruments were valid, reliable, objective, and reflective.